Role and mechanism of DNA methylation and its inhibitors in hepatic fibrosis - Lyu, Shi-Yi; Xiao, Wang; Cui, Guang-Zu; Yu, Cheng; Liu, Huan; Lyu, Min; Kuang, Qian-Ya; Xiao, En-Hua; Luo, Yong-Heng (Frontiers in Genetics, 2023)
Liver fibrosis is a repair response to injury caused by various chronic stimuli that continually act on the liver. Among them, the activation of hepatic stellate cells (HSCs) and their transformation into a myofibroblast phenotype is a key event leading to liver fibrosis, however the mechanism has not yet been elucidated. The molecular basis of HSC activation involves changes in the regulation of gene expression without changes in the genome sequence, namely via epigenetic regulation. DNA methylation is a key focus of epigenetic research, as it affects the expression of fibrosis-related, metabolism-related, and tumor suppressor genes. Increasing studies have shown that DNA methylation is closely related to several physiological and pathological processes including HSC activation and liver fibrosis. This review aimed to discuss the mechanism of DNA methylation in the pathogenesis of liver fibrosis, explore DNA methylation inhibitors as potential therapies for liver fibrosis, and provide new insights on the prevention and clinical treatment of liver fibrosis.